1893 Fla. Laws 13 § 14 - (:unkn) unknown (General Publisher, 1893)
Prohibited the keeping or selling of pistols, Springfield rifles, repeating rifles, Bowie-knives, or dirk knives by merchants, store-keepers, or dealers without paying a license tax of ten dollars. Violators punished by fined of fifty dollars, or by imprisonment in the county jail of not more than six months. Also prohibited the sale of these weapons to minors.
--
Keywords: LICENSE - DEALERS